Deficiency in Aryl Hydrocarbon Receptor (AHR) Expression throughout Aging Alters Gene Expression Profiles in Murine Long-Term Hematopoietic Stem Cells - Bennett, John A. (PLoS One, 2015)
Dysregulation of hematopoietic stem cell (HSC) signaling can contribute to the development of diseases of the blood system. Lack of aryl hydrocarbon receptor (AhR) has been associated with alterations in gene expression related to HSC function and the subsequent development of a myeloproliferative disorder in aging female mice. We sorted the most primitive population of HSCs with the highest stem cell potential (Long-term, or LT-HSCs) from 18-month-old AhR-null-allele (AhR-KO) and WT mice and analyzed gene expression using microarray to determine alterations in gene expression and cell signaling networks in HSCs that could potentially contribute to the aging phenotype of AhR-KO mice. Comparisons with previous array data from 8-week old mice indicated that aging alone is sufficient to alter gene expression. In addition, a significant number of gene expression differences were observed in aged LT-HSCs that are dependent on both aging and lack of AhR. Pathway analysis of these genes revealed networks related to hematopoietic stem cell activity or function. qPCR was used to confirm the differential expression of a subset of these genes, focusing on genes that may represent novel AhR targets due to the presence of a putative AhR binding site in their upstream regulatory region. We verified differential expression of PDGF-D, Smo, Wdfy1, Zbtb37 and Zfp382. Pathway analysis of this subset of genes revealed overlap between cellular functions of the novel AhR targets and AhR itself. Lentiviral-mediated knockdown of AhR in lineage-negative hematopoietic cells was sufficient to induce changes in all five of the candidate AhR targets identified. Taken together, these data suggest a role for AhR in HSC functional regulation, and identify novel HSC AhR target genes that may contribute to the phenotypes observed in AhR-KO mice.